The Influence of Nct Dream as Brand Ambassador on Brand Image of Lemonilo Instant Noodle Product Through Young Generation - Tridayanti, Famelia; Nurfebiaraning, Sylvie (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2022)
Based on data from WINA (World Instant Noodle Association), Indonesia ranks second as the country with the most demand for instant noodles. The high consumption rate of Indonesian instant noodles and the rise of health problems related to instant noodles are the main reasons Lemonilo presents instant noodles that are healthier and more convenient to consume. Lemonilo collaborated with the K-pop music group from South Korea, NCT DREAM as brand ambassadors to support its marketing communications. This is a form of influence of the Korean Wave, the term for the spread of Korean culture globally, including in Indonesia. This study aims to determine whether and how much influence NCT DREAM as a brand ambassador has on the brand image of Lemonilo instant noodle products in the younger generation. The indicators tested in this study are brand ambassadors as independent variables with sub-variables visibility, credibility, attraction, and power, and brand image as the dependent variable with sub-variables strength of brand association, favorable of brand association, and uniqueness of brand association. . This type of research is associative with quantitative methods. The population of this study is the young generation aged 16-30 years with simple random sampling of 385 respondents through questionnaires. The results showed that there was a significant effect of NCT DREAM as a brand ambassador on the brand image of Lemonilo instant noodle products by 39.8% while the rest was influenced by other factors outside of this study.